Emergency nurses' attitudes toward interprofessional collaboration and teamwork and their affecting factors: A cross-sectional study - Sanaz Rezaei; Fariborz Roshangar; Azad Rahmani; Faranak Jabbarzadeh Tabrizi; Parvin Sarbakhsh; Kobra Parvan (Kashan University of Medical Sciences, 2021)
Background: The emergency department (ED) is a multidisciplinary department and seriously needs interprofessional collaboration (IPC). Objectives: The purpose of this study was to examine the emergency nurses' attitudes toward IPC and teamwork and their affecting factors. Methods: A cross-sectional study was conducted on 138 emergency nurses working in teaching hospitals affiliated to Tabriz University of Medical Sciences, Tabriz, Iran, from January to April 2019. Data were collected using a three-part questionnaire including a demographic data sheet, the Jefferson Scale of Attitudes toward Physician-Nurse Collaboration, and the Testing Team Attitude Questionnaire. The data were analyzed using descriptive statistics, Pearson's correlation coefficient, analysis of variance, and multivariate regression analysis. Results: The majority of the study participants were female (68.1%), in the age range of 30-40 years old (44.2%), and had a working experience of 1-5 years in the ED (63.8%). The mean scores of nurses' attitudes toward IPC and teamwork were 48.68 ± 5.14 and 96.15 ± 8.97, respectively. A direct and strong correlation was found between nurses' attitudes toward IPC and teamwork (r = 0.594, P = 0.001). Regression analysis showed that, among all variables, only the participants' employment status (compulsory governmental services, P < 0.031 and B = 2.356), overall work experience between 1 and 5 years (P < 0.001 and B = -3.769), and the attitude toward teamwork (P < 0.001 and B = 0.350) could significantly predict nurses' attitude toward IPC. Conclusion: The attitudes of emergency nurses toward IPC and teamwork were at an optimal level. Nurses' belief in IPC and especially belief in nurse-physician collaboration plays an important role in providing quality care and keeping patient safety in ED. Joint in-service workshops on the philosophy and principles of IPC and teamwork for nurses and physicians working in EDs can further strengthen the IPC.